Concrete of 210 kg/cm2 with Addition of Recycled Glass Before Pathogenic Agents (LACCEI, 2024)
This investigation was carried out with the purpose of analyzing the compressive strength of concrete f'c=210 kg/cm2 with recycled glass added in percentages of 5%, 10% and 15% and exposed to sulfuric acid during the process of cured. 108 test tubes were analyzed and applied in 4 groups of 27 according to control design, 5%, 10% and 15% Inclusion and exclusion techniques were used as the basis for this research. As data collection instruments, formats were used to support the tests carried out in the laboratory, in order to synthesize and organize the relevant information. Finally, the results of the resistance of the 108 test tubes were analyzed, concluding that the resistance increased according to the age of curing and the percentage added.